Palliative pelvic radiotherapy for symptomatic rectal cancer – a prospective multicenter study. (1st December 2016) - Cameron, Marte G.; Kersten, Christian; Vistad, Ingvild; van Helvoirt, Rene; Weyde, Kjetil; Undseth, Christine; Mjaaland, Ingvil; Skovlund, Eva; Fosså, Sophie D.; Guren, Marianne G.
Abstract: Background and purpose: Palliative pelvic radiotherapy (PPRT) is used to treat locally advanced rectal cancer (RC) although symptomatic effects and toxicities are poorly documented. Aims were to evaluate symptom severity, quality of life (QOL) and toxicity after PPRT. Material and methods: Fifty-one patients with symptomatic primary or recurrent RC prescribed PPRT with fractions of 3 Gy to 30–39 Gy were included. Primary outcome was severity of target symptoms (TS) 12 weeks after PPRT. Pelvic symptom burden, toxicity, and QOL were assessed. Response was defined as patient-reported TS improvement or resolution. Results: Pain (n = 24), rectal dysfunction (n = 16), and hematochezia (n = 9) were the most common TSs. Overall response rate among evaluable patients 12 weeks after PPRT was 28/33 (85%). Eighteen patients did not complete the study follow-up, 16 due to deteriorating health. TS responses were 10/13 (77%) for pain, 9/10 (90%) for rectal dysfunction, and 8/8 for hematochezia. Non-target pelvic symptom severity decreased and median QOL scores remained stable. There was no grade 4 toxicity. Median survival was nine months. Conclusions: In the majority of patients with symptomatic primary or recurrent RC, PPRT with 30–39 Gy contributes to pelvic symptom relief, with little toxicity. Patients prescribed PPRT of RC have limited life expectancy. Future studies should investigate simplification of PPRT.